Computerized Working Memory Battery (BIMeT-V): Studying the Relation between Working Memory, Verbal Reasoning and Reading Comprehension - Barreyro, Juan Pablo (2019)
Working memory refers to all the systems and processes linked to the maintenance and active retention of information relevant to the performance and execution of complex cognitive tasks. Individual diff erences in working memory have been shown to explain diff erences in other cognitive abilities, such as comprehension and reasoning. The purpose of the present work was to study the relationship between verbal working memory, verbal reasoning and text comprehension, for which a verbal working memory battery was designed and validated: The verbal Computerized Working Memory Battery (Batería Informatizada de Memoria de Trabajo Verbal [BIMeT-V]). Results showed that the tests administered presented a very good reliability due to internal consistency and, in terms of validity, two latent factors saturated the tests: one of storage and one of storage and concurrent processing of verbal information. Likewise, verbal reasoning skills and the ability to comprehend expository texts are supported by working memory’s concurrent storage and processing of verbal information, and to a lesser extent, or with a lesser role, the verbal information storage component.